Efficacy of human HC016 cell transplants on neuroprotection and functional recovery in a rat model of acute spinal cord injury. (26th December 2019) - Maqueda, Alfredo; Rodriguez, Francisco J.
Abstract: Spinal cord injury (SCI) is a devastating event with huge personal and social costs, for which there is no effective treatment. Cell therapy constitutes a promising therapeutic approach for SCI; however, its clinical potential is seriously limited by their low survival in the hostile conditions encompassing the acute phase of SCI. Human HC016 (hHC016) cells, generated from expanded human adipose mesenchymal stem cells (hAMSCs) and pulsed with a patented protocol with hydrogen peroxide (H2 O2 ), are expected to acquire improved resistance to oxidative environments which appears as a major limiting factor hampering the engrafting success. Our specific aim was to assess whether H2 O2 ‐pulsed hHC016 cells had an improved survival and thus therapeutic efficacy in a rat contusion model of acute SCI when grafted 48 hr after injury. Functional recovery was evaluated up to 56 days post‐injury (dpi) by locomotor (open field test and CatWalk) and sensory (Von Frey and Hargreaves) tests. Besides, histological evaluation of transplanted cell survival and tissue protection/regeneration was also performed. Functional results showed a statistically significant improvement on locomotor recovery outcomes with hHC016 cells. Accordingly, superior cell survival in correlation with long‐term neuroprotection, higher axonal regeneration, and reduced astroglial and microglial reactivity was also observed with hHC016 cells. These results demonstrate an enhanced survival capacity of hHC016 cells resulting in improved functional and histological outcomes as compared with hAMSCs, indicating that hHC016 cell transplants may constitute a promising cell therapy for acute SCI.